Maternal age of menarche is not associated with asthma or atopy in prepubertal children. Issue 10 (29th July 2005) - Maitra, A; Sherriff, A; Northstone, K; Strachan, D; Henderson, A J
Abstract : Background: Maternal sex hormones in pregnancy can theoretically influence the developing fetal immune system and modulate the subsequent development of atopic disorders. Early onset of menarche has been linked to increased oestrogen levels in adult women. A study was undertaken to examine the association between early onset menarche in pregnant women and asthma and atopic status of their children at 7 years of age. Methods: The Avon Longitudinal Study of Parents and Children (ALSPAC) is a longitudinal birth cohort study in which pregnant women, resident in Avon (UK), were recruited on the basis of an expected date of delivery between 1 April 1991 and 31 December 1992. Maternal age at menarche was assessed from prenatal questionnaires administered to the women. Clinical outcomes in the children were based on mothers' responses to self-completion questionnaires and included asthma, eczema, and hay fever. The atopic status of the child was objectively assessed by skin prick tests to a panel of common aeroallergens at the age of 7 years. Analyses used multivariable logistic regression with a diverse range of possible confounders. Results: Complete data were available on 5765 woman and child pairs. The prevalence of ever reported asthma to 7 years was 20.4%, eczema 58.6%, hay fever 12.1%, and atopy (defined as any positive (>2 mm weal) response) was present in 20.6%. There were no significant differences in mean age of menarche between mothers of children with and without each of the primary outcomes. Adjusted odds ratios (95% CI) for the latest age of menarche (16+ years) compared with the lowest (<12 years) reference group were 1.41 (1.00 to 1.99) for asthma, 0.98 (0.73 to 1.91) for eczema, 0.95 (0.62 to 1.44) for hay fever, and 0.98 (0.68 to 1.42) for atopy. Conclusion: No consistent association was found between maternal age at menarche and asthma, eczema, hay fever or atopy in their children during early childhood.